Perancangan dan Implementasi Aplikasi Penerimaan Peserta Didik Baru (PPDB) Pada MAN 1 Pidie Jaya Berbasis Website - Muhammad Danil; Baihaqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information technology has encouraged educational institutions to adopt digital systems in administrative management, including the New Student Admission (Penerimaan Peserta Didik Baru/PPDB) process. MAN 1 Pidie Jaya still implements a manual registration system, which results in several problems such as long queues, data recording errors, and limited access for prospective students from outside the region. This study aims to design and implement a web-based PPDB application to improve the effectiveness and efficiency of the new student admission process at MAN 1 Pidie Jaya. The system development method used is the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The application was developed using PHP Native as the programming language and MySQL as the database. The results show that the web-based PPDB system is able to facilitate online registration, manage prospective student data in a structured manner, and deliver information and selection results quickly and transparently. The implementation of this system provides convenience for prospective students in the registration process and assists the school in improving the quality of PPDB administrative services. Therefore, the web-based PPDB application is considered feasible and effective to be implemented as a digital solution at MAN 1 Pidie Jaya